SMARCA4-inactivating mutations increase sensitivity to Aurora kinase A inhibitor VX-680 in non-small cell lung cancers - Vural Tagal (Nature Portfolio, 2017)
Lung cancers often harbour loss-of-function mutations inSMARCA4. Here, the authors demonstrate a vulnerability of SMARCA4-deficient lung cancers for Aurora kinase A inhibition associated with mitotic defects.